Profile of Anaemia in HIV Positive Patients - Bhusal, Khem Raj; Devkota, Surya; Shrestha, Midhan; Khadga, Prem (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: This was a cross-sectional observational study designed to see the prevalence of anemia among HIV positive patients and its correlation with CD4 counts. Materials & Methods: Fifty five HIV/AIDS patients presented for the first time to Tribhuwan University Teaching Hospital [TUTH] were enrolled in the study. Patients' duration of HIV positivity, history regarding ART and duration, history of associated co morbid or opportunistic conditions were taken, CD4 counts, RFT, CBC test results were recorded. Patients' clinical and laboratory parameters were recorded. Anaemia was classified by WHO criteria for both men and women. Results: Out of 55 patients, 23 (42 %) had anemia, out of which 14 (60.87 %) had mild anemia (anemia but Hb not less than 9.5g/dl), four (17.39%) had moderate anemia (Hb 8 to 9.4 g/ dL) and two (8.7%) had severe anemia (Hb 6.5 to 7.9 g/dL) and three (13.04%) had very severe or life threatening anemia (Hb less than 6.5 g/dL). Corresponding odds ratio from stage CD4 counts<200 to CD4 counts >/= 200 for anemia was 4.55 times; which is statistically significant (p<0.0001). There was negative association between the prevalence of anemia and HIV stage (CD4 count). Conclusion: There was high prevalence of anemia and severity of immunodeficiency directly correlates with degree of anemia. Degree of anemia can be easily assessed even in rural clinical setting, hence degree of immunodeficiency can early be detected in all settings. JCMS Nepal. 2016;12(2):70-3